Concepciones de niñez e identidad en las experiencias escolares de niños mapuche del Neuquén - Szulc, Andrea (2015)
Elementary schools continue to play a central role today in mapuche rural communities, at neuquén —Argentina—, sometimes, as the only government enclave. In the school context, thus, the hegemonic definition of identity is reinforced, as well as the school’s model of childhood. such identity relegates mapuche culture and subordinates it to the national, provincial and catholic identity. Anthropologi- cal research carried out since 2001 has been showing how some mapuche children and adolescents question school’ conceptions.This article presents a brief description of the educational system in this region, and explores the school experiences of mapuche children, examining the disputes over conceptions of childhood and mapuche identity introduced by children’ resistance practices. Considering mainly original ethnographic materials, the analysis reveals how through this controversial attitude not only they have strengthened their self recognition as mapuche but also they havebeen «succesfull» in the educational system.